Comparative Analysis of Gut Microbiota in Humans Living with and Without Companion Animals - Kyung-Hyo Do; Jiwon Park; Nahee Kim; Dahye Ryu; Min-Gyu Kim; Hyunjung Ahn; Hakhyun Kim; Jun-Gi Hwang; Min-Kyu Park; Kwang-Won Seo; Wan-Kyu Lee (Life)
Cohabitation with companion animals (CAs) has been suggested as a significant modifier of gut microbial diversity. This study investigated the influence of cohabitation with CAs on human gut microbiota composition. Using 16S rRNA gene sequencing, we analyzed the gut microbiota of 20 families with CAs (40 adults, 20 children) and 20 families without CAs (40 adults, 20 children). Alpha and beta diversity analyses were performed, and the differentially abundant genera were identified. There were significant differences in beta diversity across the groups (p-value = 0.001). The Bacillota/Bacteroidota ratio was considerably lower in the CAs group (0.67) than in the without-CAs group (1.02). Prevotellaceae_UCG-003 (log2 fold change: 7.3; adjusted p-value ≤ 0.001), Ruminococcaceae (log2 fold change: 6.3; adjusted p-value ≤ 0.001), and Oscillospira (log2 fold change: 5.1; adjusted p-value = 0.012) were elevated in the group cohabiting with CAs, whereas Megamonas (with CAs: 3.81%; without CAs: 13.52%) and Veillonella (with CAs: 3.77%; without CAs: 6.50%) were more prevalent in the group without CAs. Cohabitation with CAs may positively influence the gut microbiota by promoting the presence of beneficial bacteria and reducing the Bacillota/Bacteroidota ratio. This study highlights the potential for cohabitation with CAs to promote gut microbial health.